SYNTAX Scoring In Patients with Coronary Artery Disease and Its Effect on Mode of Revascularization , Single Center Experience. - Al Saffar, Hilal B.; Zedan, Saad M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: revascularization therapy for patients with left main (LM) and/or three vessel coronary disease is a matter of argument for long a time whether bypercutaneous coronary angiography orcoronary artery bypass grafting. SYNTAX trial was designed to assess the optimal revascularization strategy between percutaneous coronary intervention and coronary artery bypass grafting, for patients with left main stem coronary artery disease and/or 3-vessel coronary disease.Aim: To estimate the complexity of coronary artery disease in patients referred to a tertiary Iraqi cardiac center and its effect on mode of revascularization.Patients and Method: Ninety nine patients who were referred to Iraqi center for heart disease from July to December 2010 withthe diagnosis of CAD were included. Full history, clinical examination, biochemical tests ( blood sugar ,total cholesterol , blood urea and serum creatinine) were checked, electrocardiographic and echocardiographic characteristics were analyzed .All patients underwent diagnostic angiography andSYNTAX score calculator was applied and the SYNTAX score was recorded.Patients  were divided into two groups :  group A  , thosewho were  planned for PCI  and group B who were planned for  CABG .Results: Mean age of the patients was 57.6±10.6, ranging 19-80 year, male were more than female (75.8% vs. 24.6%). Risk factors prevalencewas DM (42.6%), high blood pressure (52.8 %), smoking (42.4%), hypercholesterolemia (43.4%) and prior MI (32.3%).Mean age of group A was 54.22±11.27 while group B was 62.37±7.47 (P value 0.0001) . There was no significant difference in risk factors prevalence between group A and B ( DM  36.2% vs.51.2% p=0.31), hypertension(53.4% vs.53.3% p=0.98),  smoking (41.3% vs.43.9% p=0.8), hypercholestoemia (31% vs. 60.9%),ejection fraction